Molecular Typing of Syphilis-Causing Strains Among Human Immunodeficiency Virus-Positive Patients in Antwerp, Belgium - Mikalová, Lenka; Grillová, Linda; Osbak, Kara; Strouhal, Michal; Kenyon, Chris; Crucitti, Tania; Šmajs, David (Sexually transmitted diseases, 2017)
Centers for Disease Control and Prevention and sequencing-based treponeme typing was used to analyze 72 blood samples, collected from human immunodeficiency virus and syphilis co-infected patients during 2014 to 2015 in Antwerp, Belgium. Twenty-nine (40.3%) isolates were polymerase chain reaction positive for Treponema pallidum, and all tested were macrolide-resistant. Four genotypes were identified by sequencing-based typing including two new genotypes, U4NR8 and SU9R8, whereas enhanced Centers for Disease Control and Prevention typing revealed 7 subtypes.
Keywords: Molecular Typing; Macrolides; Humans; Belgium; syfilis; RNA, Ribosomal, 23S; RNA ribozomální 23S; Polymorphism, Restriction Fragment Length; lidé středního věku; Female; dospělí; Genotype; lidé; antibakteriální látky; Adult; Belgie; ženské pohlaví; bodová mutace; Anti-Bacterial Agents; Male; Middle Aged; Drug Resistance, Bacterial; molekulární typizace; Point Mutation; Syphilis; genotyp; bakteriální léková rezistence; polymorfismus délky restrikčních fragmentů; Treponema pallidum; HIV Seropositivity; mužské pohlaví; HIV séropozitivita; makrolidy